Attempting palaeoenvironmental reconstructions in war-torn zones: the case of the Okavango source wetlands in Angola - Singh, Meriska (My University, 2019)
are an increasing number of palaeoenvironmental reconstructions for southern Africa. Palaeoenvironmental reconstructions using pollen as a proxy tool are limited in southern Africa due to large areas of arid environments and the difficulty of accessing sites. The Okavango is an important biological region, and there have been a few studies done in the delta itself, but nothing in the source waters. In Angola, the absence of studies is mainly due to the civil war (1974-2002), which prevented access into the region and post-war as well due to the presence of landmines. Following this war remains an ongoing effort to demine the area. The National Geographic Okavango Wilderness Project is an initiative to protect the Okavango Delta as well as its source tributaries located in the Angolan Highlands. The goal is to study endemic species and inform conservation strategies. This is a pioneering attempt at a palaeoenvironmental reconstruction in this wartorn region. The sediment profile represents flora similar to the contemporary record with fluctuations with a depth that can broadly reveal changes in moisture dynamics. This would be useful in understanding the palaeo-hydro-climate of the broader Okavango system. However, radiocarbon AMS dates reveal that the material only spans the past 200 years with significant overturning. What was anticipated to be a Holocene core, turned out to be upturned material due to post-depositional disturbance. This reveals the long-lasting effects of the war due to landmines to the contemporary environment and the ability to reconstruct past environments from these sites.
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Science School of Geography, Archaeology and Environmental Studies, August 2019